Carbon-coated Sn composite material and preparation method and application thereof
By controlling the concentration of tin salt aqueous solution, the amount of sodium chloride added and the high-temperature carbonization temperature, a carbon-coated Sn composite material with uniform thickness was prepared, which solved the problem of low coulombic efficiency in the existing technology and realized the application of high-efficiency and low-cost Sn-based negative electrode materials.
Patent Information
- Application Number
- CN202510833465.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-09-23
AI Technical Summary
In the existing technology, the first coulombic efficiency of carbon-coated Sn composite materials is not high, and the preparation process cost is high, which makes it difficult to meet industrialization needs.
By controlling the concentration of tin salt aqueous solution, the amount of sodium chloride added and the high-temperature carbonization temperature, a carbon-coated Sn composite material was prepared to form a carbon coating layer with uniform thickness. Combined with multi-stage carbonization treatment, the Sn lattice spacing and the performance of the carbon coating layer were optimized.
High first coulombic efficiency and high reversible specific capacity were achieved, which significantly improved the electrochemical performance of Sn-based negative electrode materials and reduced the preparation cost.
Smart Images

Figure CN120690831A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, in particular to a carbon-coated Sn composite material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries (SIBs), as the core of new energy storage technology, have become a key technology for large-scale energy storage systems due to their abundant raw material resources, long cycle life, and environmental friendliness. Ideal anode materials for SIBs should possess high specific capacity, good cycle stability, excellent rate capability, and a low potential plateau. In this context, Sn-based anode materials have become an important research direction for SIBs due to their high theoretical specific capacity, moderate sodium ion diffusion barrier, and abundant resources.
[0003] However, Sn-based anode materials face two major challenges in practical application: first, large volume expansion (up to 400% during the sodiumization process), leading to pulverization of the electrode material and rapid capacity decay; second, relatively low electronic conductivity, which affects the rate performance of sodium-ion batteries. These challenges limit the practical application of Sn-based anode materials in sodium-ion batteries.
[0004] To address the volume expansion and conductivity issues of Sn-based anode materials, researchers have proposed various strategies, including carbon coating, ultrafine nanostructure preparation, composites with conductive materials, heterostructure construction, and the introduction of oxygen vacancies. These methods have improved the electrochemical performance of Sn-based materials to some extent, but they still have some limitations. For example, while nanostructured materials can alleviate the volume expansion problem, their preparation process is complex and costly; while the conductivity of composite materials is improved, the composite process may lead to a decrease in mechanical properties; and while the introduction of heterostructures and oxygen vacancies can improve the electrochemical performance of materials, their stability and reproducibility require further verification. Generally speaking, carbon coating is the most common and relatively simple method. However, typical carbon coating agents, such as dopamine hydrochloride and phenolic resin, are relatively expensive. Some researchers have reacted sodium alginate with tin salts to form a gel, which is then calcined to produce porous carbon-coated nano-Sn. This carbon coating method is relatively simple to operate and has low coating costs, but the initial coulombic efficiency of the product obtained by coating generally does not exceed 60%. Therefore, the existing technology also performs nitrogen doping, phosphorus doping, or further coats a layer of metal oxide on the outside of the carbon coating layer. Although this can improve the initial efficiency, the preparation difficulty and cost are significantly increased, which is not conducive to industrial and large-scale production.
[0005] For this purpose, this application is filed. Summary of the Invention
[0006] In view of the problem in the prior art that the first coulombic efficiency is low when preparing a carbon-coated Sn composite material by reacting sodium alginate with a tin salt, the present invention provides a carbon-coated Sn composite material and a preparation method and application thereof.
[0007] First, the present invention proposes a carbon-coated Sn composite material, which is a carbon-coated Sn core-shell structure, with a carbon coating layer thickness of 18-28nm. TEM test shows that the lattice spacing of Sn is 2.78- XRD test shows that the diffraction angle of Sn(101) peak is 31.84-32.02°, and the carbon-coated Sn composite material also contains 306-387ppm of Na + .
[0008] Furthermore, when the carbon-coated Sn composite material is used as the negative electrode material for sodium-ion batteries, the discharge cut-off voltage is 0V and the charge cut-off voltage is 2.0V under charge-discharge tests at a current density of 0.1C, and its capacity is greater than 540mAh / g.
[0009] Furthermore, its capacity is 541-586 mAh / g.
[0010] Secondly, the present invention provides a method for preparing a carbon-coated Sn composite material, comprising the following steps:
[0011] S1, dissolving a tin salt in water to form a tin salt aqueous solution, then adding sodium chloride, stirring and dissolving to form a mixed solution;
[0012] S2, dissolving sodium alginate in water to form a sodium alginate sol;
[0013] S3, adding the sodium alginate sol obtained in S2 dropwise to the mixed solution obtained in S1, performing cross-linking reaction at room temperature and centrifuging to obtain a white granular product, which was then dried;
[0014] S4, subjecting the product obtained in S3 to a multi-stage carbonization treatment under an inert atmosphere to obtain a final product, wherein the multi-stage carbonization treatment includes pre-carbonization and high-temperature carbonization;
[0015] Wherein: the concentration of the tin salt aqueous solution is represented by c, and the unit is mol / L; the amount of sodium chloride added is represented by a, and the unit is g; the thickness of the carbon coating layer in the composite material is represented by h, and the unit is nm; the temperature of high-temperature carbonization is represented by T, and the temperature is ° C; the lattice spacing of Sn in the composite material is represented by d, and the unit is nm; the above parameters meet the following requirements: 0.89≤c*a*h / (T*d)≤1.44.
[0016] In the present invention, the concentration c of the tin salt aqueous solution, the amount of sodium chloride added a, the thickness h of the carbon coating layer, the high-temperature carbonization temperature T and the lattice spacing d of Sn in the composite material are closely related: an increase in the concentration c of the tin salt aqueous solution will cause the thickness h of the carbon coating layer to first thicken and then thin, an increase in the amount of sodium chloride added a will cause the thickness h of the carbon coating layer to thicken, an increase in the high-temperature carbonization temperature T will cause the thickness h of the carbon coating layer to thin and densify, and repair the loose carbon layer caused by the low concentration c of the tin salt aqueous solution; an increase in the concentration c of the tin salt aqueous solution will cause the Sn lattice to expand, the lattice spacing d to increase, and the diffraction angle of the Sn (101) peak to decrease; an increase in the high-temperature carbonization temperature T will lead to an increase in the crystallinity of the Sn particles, a decrease in defects, lattice contraction, a decrease in the lattice spacing d, and an increase in the diffraction angle of the Sn (101) peak. In addition, the dense carbon layer will squeeze the Sn particles, causing lattice distortion, further increasing the diffraction angle of the Sn (101) peak. The present invention unexpectedly discovered that when the above parameters meet the requirement of the above formula: 0.89≤c*a*h / (T*d)≤1.44, the corresponding carbon-coated Sn composite material has good first coulombic efficiency and capacity after being used in sodium ion batteries, especially the first coulombic efficiency, which is significantly better than the existing technology. Therefore, by regulating the concentration c of the tin salt aqueous solution, the amount of sodium chloride added a, and the high-temperature carbonization temperature T in the preparation conditions, a product with a defined carbon coating layer thickness, a defined Sn lattice spacing, and a defined Sn (101) peak diffraction angle can be obtained, and combined with the above formula, a carbon-coated Sn composite material with high first efficiency can be screened.
[0017] Further, the molar ratio of tin salt to sodium alginate is 2.5-5, for example, specifically 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5, etc.; the molar ratio of tin salt to sodium chloride is 0.59-1.18, for example, specifically 0.5, 0.52, 0.55, 0.58, 0.6, 0.62, 0.65, 0.68, 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 1, etc.;
[0018] In this embodiment, the molar ratio of tin salt to sodium alginate is 2.5-5. At this time, a part of the tin ions is used to cross-link with the carboxyl groups in the sodium alginate and form a carbon coating after carbonization, and the other part of the tin ions is reduced to form tin cores. An appropriate excess of tin salt helps to obtain a carbon-coated Sn composite material with a higher Sn content. For example, if the molar ratio of tin salt to sodium alginate is less than 2.5, the amount of tin ions is insufficient, which can easily lead to insufficient cross-linking, the resulting carbon coating is too thin, and the initial tin core formation is more difficult. The resulting carbon-coated Sn composite material has a low Sn content, which is not conducive to the specific capacity of the material. If the molar ratio of tin salt to sodium alginate is greater than 5, the tin ions are excessive. Although the cross-linking is sufficient, the size of the tin core will be significantly increased, which will lead to a too thin carbon coating layer, and the proportion of active material tin is too high and the carbon content is too low, which seriously damages the electrical conductivity and the ability to alleviate volume expansion of the composite material, thereby reducing its cycle stability as an electrode material.
[0019] In this embodiment, an appropriate amount of sodium chloride can effectively reduce the viscosity of the sodium alginate sol. When the sodium alginate sol is added dropwise to the tin salt aqueous solution to which sodium chloride is added, the tin salt can diffuse better in the sodium alginate solution, thereby promoting a more uniform cross-linking reaction, avoiding local cross-linking or insufficient cross-linking, and helping to obtain a carbon coating layer with uniform thickness. Moreover, during the cross-linking process, Na + It can also fill the gaps in the cross-linked network to a certain extent, enhance the stability of the cross-linked network, and reduce the destruction of the cross-linked structure caused by changes in the external environment such as pH fluctuations and temperature changes; the carbon coating layer has a uniform thickness, and the Sn particles are evenly dispersed in it. The synergistic effect is beneficial to alleviate volume expansion, increase structural stability, and provide more active sites, increasing the interaction between the carbon-coated Sn composite material and the Na in the electrolyte. + The contact area is large, thereby improving the initial efficiency and capacity of the composite material; the present invention has confirmed through creative work that when the molar ratio of tin salt to sodium chloride is 0.59-1.18, sodium chloride can promote the formation of a carbon coating layer with uniform thickness and uniform dispersion of Sn particles in the carbon coating layer, providing more active sites, without causing Na + Too much residue will affect battery preparation.
[0020] Preferably, the concentration of the tin salt aqueous solution is 1-2 mol / L, for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 mol / L, etc.; the mass percentage of the sodium alginate sol is 8%-12%, for example, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, etc.;
[0021] In this embodiment, sodium alginate is a direct carbon source. The higher the concentration of sodium alginate, the greater the total amount of material that can be converted into carbon per unit volume, the greater the density of the cross-linked network formed, and the thicker the carbon coating layer formed after carbonization. However, if the concentration is too high, the viscosity of the sodium alginate sol will be too high, affecting the uniformity of mixing with the tin salt aqueous solution, which in turn will lead to local concentration differences and affect the uniformity of the carbon coating layer. Therefore, the present invention limits the mass percentage of the sodium alginate sol to 8%-12%. Within this concentration range, it ensures the formation of a carbon coating layer of moderate thickness without affecting the fluidity and mixing uniformity of the sol.
[0022] In this embodiment, the carboxyl groups in the sodium alginate undergo a cross-linking reaction with the tin ions in the tin salt, and a carbon coating is formed after carbonization. Based on the determination of the amount of carbon source, the concentration of the tin salt also has a great influence on the thickness of the carbon coating. For example, if the concentration of the tin salt is too low, the number of tin ions participating in the cross-linking reaction per unit volume is small, and the number of sites that can undergo cross-linking reaction with the sodium alginate is relatively small, and the resulting carbon coating is too thin. For example, if the concentration of the tin salt is too high, the number of tin ions participating in the cross-linking reaction per unit volume is large, and the number of sites that can undergo cross-linking reaction with the sodium alginate is relatively large, the cross-linking network density increases, and the resulting carbon coating is too thick. A carbon coating that is too thin is likely to cause the material structure to pulverize during circulation, and a carbon coating that is too thick will lead to degradation of the first efficiency and capacity of the material. Therefore, the present invention limits the concentration of the tin salt aqueous solution to 1-2 mol / L. Within this concentration range, the tin ions can both react with the above The carboxyl groups in the sodium alginate within the above-mentioned concentration range are fully cross-linked to form a dense cross-linked network, and a continuous, uniform, and appropriately thick carbon coating layer is formed after carbonization. This ensures that sufficient tin ions are reduced to initial tin nuclei within the cross-linked network and aggregate and grow during the subsequent drying, pre-carbonization, and carbonization processes. The inventors have found that if the concentration of the tin salt aqueous solution is less than 1 mol / L, which is too low relative to the sodium alginate sol with a mass percentage of 8%-12%, the cross-linking is insufficient, the network structure formed is loose, and the carbon coating layer obtained after carbonization has poor continuity, is porous, and is thin. If the concentration of the tin salt aqueous solution is greater than 2 mol / L, which is relatively high relative to the sodium alginate sol with a mass percentage of 8%-12%, although the cross-linking is sufficient, it will significantly induce the formation of large tin particles, which ultimately leads to a relatively thin or even incomplete carbon coating layer.
[0023] The concentration of tin salt and sodium alginate needs to match to form an ideal carbon-coated Sn composite material. The present invention has confirmed through creative labor that a tin salt aqueous solution with a concentration of 1-2 mol / L and a sodium alginate sol with a mass percentage of 8%-12% can help obtain a carbon-coated carbon-coated Sn composite material with an appropriate thickness. The carbon-coated Sn composite material has a low volume expansion rate and good cycle stability, and has a high first coulombic efficiency and reversible specific capacity when used as a negative electrode material for sodium ion batteries.
[0024] Furthermore, in step S3, stirring is continued during the cross-linking reaction, and the room temperature refers to 16-25°C, for example, it can be 16, 17, 18, 19, 20, 21, 22, 23, 24, 25°C, etc. The cross-linking reaction time is 10-15h, for example, it can be 10, 11, 12, 13, 14, 15h, etc.
[0025] Furthermore, in step S4, the temperature of the pre-carbonization is 500-700°C and the time is 0.5-5 hours, and the temperature of the high-temperature carbonization is 900-1100°C and the time is 2-6 hours.
[0026] In this embodiment, the main function of pre-carbonization is to stabilize the precursor structure, prevent melting / agglomeration, and retain the prototype of the carbon skeleton; high-temperature carbonization is used to achieve graphitization of the carbon layer, enhance conductivity / mechanical strength, and optimize the tin crystallization state; the carbonization temperature, especially the high-temperature carbonization temperature, has a great influence on the performance of the carbon coating layer. The appropriate high-temperature carbonization temperature can not only control the thickness and stability of the carbon coating layer, making it moderately thick, uniform, and tough, but also retain the pore structure of the carbon coating layer, without affecting the active sites of the composite material and without degrading the capacity; the high-temperature carbonization temperature should not be too low or too high. If it is too low, stable metal Sn cannot be formed in the composite material. If it is too high, Sn tends to combine with carbon, which easily leads to an increase in the Sn layer spacing.
[0027] Furthermore, the tin salt is a +2-valent or / and +4-valent water-soluble tin salt, specifically tin dichloride, tin tetrachloride, tin nitrate, tin sulfate, etc., preferably a +4-valent water-soluble tin salt.
[0028] Thirdly, the present invention provides a negative electrode sheet comprising the above-mentioned carbon-coated Sn composite material.
[0029] Fourthly, the present invention proposes a sodium ion battery containing the above-mentioned negative electrode sheet; the sodium ion battery also includes an electrolyte, a separator, and a positive electrode sheet. The active materials, electrolyte, separator, etc. on the positive electrode sheet are all conventional technical means in this field.
[0030] Furthermore, it passed the charge and discharge test at a current density of 0.1C, with a discharge cut-off voltage of 0V, a charge cut-off voltage of 2.0V, and an initial coulombic efficiency of >62%;
[0031] Furthermore, its first coulombic efficiency is 62.4%-67.6%.
[0032] Compared with the prior art, the present invention uses a tin salt aqueous solution and a sodium alginate sol of appropriate concentration as raw materials, and adds sodium chloride. By controlling the molar ratio of the tin salt to the sodium alginate and the molar ratio of the tin salt to the sodium chloride, a carbon-coated Sn composite material with a first coulombic efficiency higher than 60% is prepared by means of a cross-linking reaction and a multi-stage carbonization treatment. Moreover, a carbon-coated Sn composite material with excellent electrochemical performance can be screened out by simple mathematical calculations between relevant parameters. The preparation method proposed by the present invention is simple to prepare and operate, requires conventional conditions and is low in cost. The product prepared by the present invention has a high reversible specific capacity and first coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0034] Figure 1 This is the XRD pattern of the product obtained in Example 1-1.
[0035] Figure 2 TEM of the product obtained in Example 1-1 Figure 1 .
[0036] Figure 3 TEM of the product obtained in Example 1-1 Figure 2 .
[0037] Figure 4 This is a 0.1C charge and discharge curve of the button battery assembled in Example 1-1. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, and are not all embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0039] The raw materials involved in the following examples and comparative examples were all commercially available. The devices involved in the following examples and comparative examples were all conventional devices in the art.
[0040] Example 1-1
[0041] A method for preparing a carbon-coated Sn composite material, the preparation method is as follows:
[0042] S1. Dissolve tin tetrachloride in water to form a 1 mol / L tin tetrachloride aqueous solution (the amount of tin tetrachloride is 0.1 mol) with a volume of 100 mL. Then add 10 g of sodium chloride (the amount of sodium chloride is 0.17 mol) and stir to dissolve to form a mixed solution. The molar ratio of tin tetrachloride to sodium chloride is 0.59.
[0043] S2. dissolving sodium alginate in water to form a sodium alginate sol with a mass percentage of 10% and a volume of 80 mL (the amount of sodium alginate is 0.04 mol);
[0044] S3, adding the sodium alginate sol obtained in S2 dropwise to the mixed solution obtained in S1, with a molar ratio of tin tetrachloride to sodium alginate of 2.5, and carrying out cross-linking reaction at 20°C for 12 hours, centrifuging to obtain a white granular product, and drying;
[0045] S4. The product obtained in S3 is subjected to a multi-stage carbonization treatment under nitrogen atmosphere to obtain a final product, wherein the multi-stage carbonization treatment includes pre-carbonization and high-temperature carbonization, wherein the pre-carbonization temperature is 500° C. and the time is 5 h, and the high-temperature carbonization temperature is 1000° C. and the time is 2 h;
[0046] Wherein: the concentration of the tin salt aqueous solution is represented by c, in mol / L; the amount of sodium chloride added is represented by a, in g; the thickness of the carbon coating layer in the composite material is represented by h, in nm; the temperature of high-temperature carbonization is represented by T, in °C; the lattice spacing of Sn in the composite material is represented by d, in nm;
[0047] like Figure 1 As shown: The diffraction peaks of C and Sn can be seen in the XRD pattern of the final product; Figure 2 、 Figure 3 As shown: Two types of lattices can be seen from the TEM image of the final product. The one with an interlayer spacing of 0.337 nm is C, and the one with an interlayer spacing of 0.278 nm is Sn. The coating thickness of C is 20 nm.
[0048] Example 1-2
[0049] S1. Dissolve tin tetrachloride in water to form a 1.5 mol / L tin tetrachloride aqueous solution (the amount of tin tetrachloride is 0.15 mol) with a volume of 100 mL. Then add 10 g of sodium chloride (the amount of sodium chloride is 0.17 mol) and stir to dissolve to form a mixed solution. The molar ratio of tin tetrachloride to sodium chloride is 0.88.
[0050] S2. dissolving sodium alginate in water to form a sodium alginate sol with a mass percentage of 10% (the amount of sodium alginate is 0.04 mol);
[0051] S3, adding the sodium alginate sol obtained in S2 dropwise to the mixed solution obtained in S1, with a molar ratio of tin tetrachloride to sodium alginate of 3.75, and carrying out cross-linking reaction at 25°C for 10 h, centrifuging to obtain a white granular product, and drying;
[0052] S4. The product obtained in S3 is subjected to a multi-stage carbonization treatment under nitrogen atmosphere to obtain a final product, wherein the multi-stage carbonization treatment includes pre-carbonization and high-temperature carbonization, wherein the pre-carbonization temperature is 700° C. and the time is 0.5 h, and the high-temperature carbonization temperature is 1000° C. and the time is 6 h;
[0053] Wherein: the concentration of the tin salt aqueous solution is represented by c, in mol / L; the amount of sodium chloride added is represented by a, in g; the thickness of the carbon coating layer in the composite material is represented by h, in nm; the temperature of high-temperature carbonization is represented by T, in °C; the lattice spacing of Sn in the composite material is represented by d, in nm.
[0054] Examples 1-3
[0055] A method for preparing a carbon-coated Sn composite material, the preparation method is as follows:
[0056] S1. Dissolve tin tetrachloride in water to form a 2 mol / L tin tetrachloride aqueous solution (the amount of tin tetrachloride is 0.2 mol) with a volume of 100 mL. Then add 10 g of sodium chloride (the amount of sodium chloride is 0.17 mol) and stir to dissolve to form a mixed solution. The molar ratio of tin tetrachloride to sodium chloride is 1.18.
[0057] S2. dissolving sodium alginate in water to form a sodium alginate sol with a mass percentage of 10% and a volume of 80 mL (the amount of sodium alginate is 0.04 mol);
[0058] S3, adding the sodium alginate sol obtained in S2 dropwise to the mixed solution obtained in S1, with a molar ratio of tin tetrachloride to sodium alginate of 5, and carrying out cross-linking reaction at 20°C for 12h, centrifuging to obtain a white granular product, and drying;
[0059] S4. The product obtained in S3 is subjected to a multi-stage carbonization treatment under nitrogen atmosphere to obtain a final product, wherein the multi-stage carbonization treatment includes pre-carbonization and high-temperature carbonization, wherein the pre-carbonization temperature is 600° C. and the time is 3 h, and the high-temperature carbonization temperature is 1000° C. and the time is 3 h;
[0060] Wherein: the concentration of the tin salt aqueous solution is represented by c, in mol / L; the amount of sodium chloride added is represented by a, in g; the thickness of the carbon coating layer in the composite material is represented by h, in nm; the temperature of high-temperature carbonization is represented by T, in °C; the lattice spacing of Sn in the composite material is represented by d, in nm.
[0061] Example 2-1
[0062] Compared with Example 1-1, the mass percentage of sodium alginate sol was adjusted to 8% and the volume was adjusted to 100 mL, and the rest remained the same as Example 1-1.
[0063] Example 2-2
[0064] Compared with Example 1-2, the mass percentage of sodium alginate sol was adjusted to 8% and the volume was adjusted to 100 mL, and the rest remained the same as Example 1-2.
[0065] Example 2-3
[0066] Compared with Example 1-3, the mass percentage of sodium alginate sol was adjusted to 8% and the volume was adjusted to 100 mL, and the rest were consistent with Example 1-3.
[0067] Example 3-1
[0068] Compared with Example 1-1, the mass percentage of sodium alginate sol was adjusted to 12% and the volume was adjusted to 66.7 mL, and the rest remained the same as Example 1-1.
[0069] Example 3-2
[0070] Compared with Example 1-2, the mass percentage of sodium alginate sol was adjusted to 12% and the volume was adjusted to 66.7 mL, and the rest remained the same as Example 1-2.
[0071] Example 3-3
[0072] Compared with Example 1-3, the mass percentage of sodium alginate sol was adjusted to 12% and the volume was adjusted to 66.7 mL, and the rest remained the same as Example 1-3.
[0073] Example 4-1
[0074] Compared with Example 1-1, the temperature of high-temperature carbonization was adjusted to 900° C., and the rest remained the same as Example 1-1.
[0075] Example 4-2
[0076] Compared with Example 1-2, the high-temperature carbonization temperature was adjusted to 900° C., and the rest remained the same as Example 1-2.
[0077] Example 4-3
[0078] Compared with Example 1-3, the high-temperature carbonization temperature was adjusted to 900° C., and the rest remained the same as Example 1-3.
[0079] Example 5-1
[0080] Compared with Example 1-1, the temperature of high-temperature carbonization was adjusted to 1100° C., and the rest remained the same as Example 1-1.
[0081] Example 5-2
[0082] Compared with Example 1-2, the temperature of high-temperature carbonization was adjusted to 1100° C., and the rest remained the same as Example 1-2.
[0083] Example 5-3
[0084] Compared with Example 1-3, the high-temperature carbonization temperature was adjusted to 1100° C., and the rest remained the same as Example 1-3.
[0085] Comparative Example 1-1
[0086] Compared with Example 1-1, sodium chloride was not added, and the rest were consistent with Example 1.
[0087] Comparative Example 1-2
[0088] Compared with Example 1-2, no sodium chloride was added, and the rest were consistent with Example 2.
[0089] Comparative Examples 1-3
[0090] Compared with Examples 1-3, sodium chloride was not added, and the rest were consistent with Example 3.
[0091] Comparative Example 2-1
[0092] Compared with Example 1-1, the concentration of the tin tetrachloride aqueous solution was adjusted to 3 mol / L, and the rest remained the same as Example 1-1.
[0093] Comparative Example 2-2
[0094] Compared with Example 1-1, the concentration of the tin tetrachloride aqueous solution was adjusted to 0.5 mol / L, and the rest remained the same as Example 1-1.
[0095] Comparative Example 3-1
[0096] Compared with Example 1-1, the temperature of high-temperature carbonization was adjusted to 1200° C., and the rest remained the same as Example 1-1.
[0097] Comparative Example 3-2
[0098] Compared with Example 1-2, the temperature of high-temperature carbonization was adjusted to 1200° C., and the rest remained the same as Example 1-2.
[0099] Comparative Example 3-3
[0100] Compared with Example 1-3, the high-temperature carbonization temperature was adjusted to 1200° C., and the rest remained the same as Example 1-3.
[0101] Comparative Example 4-1
[0102] Compared with Example 1-1, the temperature of high-temperature carbonization was adjusted to 800° C., and the rest remained the same as Example 1-1.
[0103] The molar ratio of tin salt to sodium alginate is represented by M1, and the molar ratio of tin salt to sodium chloride is represented by M2. The lattice spacing d of Sn and the thickness h of the carbon coating layer in each product are measured by TEM, the diffraction angle of Sn(101) peak in each product is measured by XRD, and the Na is quantified by XPS / EDS. + The calculation result of c*a*h / (T*d) is defined as the comprehensive coefficient and represented by A; the key technical parameters, product performance indicators and comprehensive coefficients involved in each embodiment and comparative example are specifically shown in Table 1.
[0104] The carbon-coated Sn composite material obtained in each embodiment and comparative example was used as a button battery negative electrode material powder, and a negative electrode sheet was prepared according to the main material: CMC: SP = 90wt%: 5wt%: 5wt%. A metal sodium sheet was used as the positive electrode, and 1 mol / L NaPF6 / EC+DEC (volume ratio 1: 1) was used as the electrolyte. A CR2032 button battery was assembled in a glove box, and the contents of H2O and O2 in the glove box were ensured to be <0.1ppm throughout the process. The CR2032 button battery was tested using a blue battery test system. The charge and discharge test was carried out at a current density of 0.1C. The discharge cut-off voltage was 0V and the charge cut-off voltage was 2.0V. The first-week reversible capacity and first-week coulombic efficiency of the test material were shown in Table 1.
[0105] Table 1
[0106]
[0107]
[0108] As shown in Table 1 and Figures 1-4 Commonly shown:
[0109] The test results of each embodiment show that the capacity of the button battery assembled in each embodiment is 541-586 mAh / g, and the first efficiency is 62.4%-67.6%. Taking Example 1-1 as an example, its first efficiency is 63.52%, the first week reversible capacity is 585.65 mAh / g, and the 0.1C charge and discharge curve is as shown in the figure. Figure 4Obviously, by adopting the preparation method proposed in the present invention, high-quality carbon coating of high-capacity Sn can be achieved in a relatively simple and low-cost manner. The coated carbon coating can effectively suppress the volume expansion and conductivity problems of Sn-based negative electrode materials, significantly improve the first efficiency, and enhance the reversible capacity.
[0110] From the comparison of the test results of Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3 with Example 1-1, Example 1-2, Example 1-3, it can be seen that: during preparation, whether sodium chloride is added or not is very important for the electrochemical properties of the product. The addition of sodium chloride can not only effectively reduce the viscosity of the sodium alginate sol, promote a more uniform cross-linking reaction, and obtain a carbon coating layer with uniform thickness, but also properly fill the gaps in the cross-linked network to enhance the stability of the cross-linked network, which is ultimately beneficial to alleviate volume expansion, increase the structural stability of the carbon coating layer, and provide more active sites. Therefore, adding an appropriate amount of sodium chloride helps to significantly improve the first effect and the first week reversible capacity.
[0111] From the comparison of the test results of Comparative Example 2-1 and Comparative Example 2-2 with Example 1-1, it can be seen that the concentration of the tin tetrachloride aqueous solution has a significant effect on the electrochemical properties of the product. Under the premise that other conditions are completely consistent, if the concentration of the tin tetrachloride aqueous solution is higher than the 1-2 mol / L specified in the present invention, such as 3 mol / L, or lower than the 1-2 mol / L specified in the present invention, such as 0.5 mol / L, it is not conducive to the first effect and capacity performance. The comprehensive coefficient A of Comparative Example 2-1 and Comparative Example 2-2 is statistically analyzed and found to be not within the range specified in this application, which is in line with expectations.
[0112] From the comparison of the test results of Comparative Example 3-1, Comparative Example 3-2, Comparative Example 3-3, Comparative Example 4-1 with Example 1-1, Example 1-2, Example 1-3, it can be seen that: if the high-temperature carbonization temperature is higher or lower than 900-1100°C specified in the present invention, such as 1200°C or 800°C, the first-week reversible capacity and first-week coulomb efficiency of the assembled button battery are much lower than the carbonization temperature of 1000°C; when the high-temperature carbonization temperature is 1200°C, the Sn interlayer spacing increases, and it can be seen that Sn has a tendency to combine with carbon, and when the high-temperature carbonization temperature is 800°C, the temperature is too low to form stable metal Sn. Both cases will lead to a decrease in capacity and first efficiency. The comprehensive coefficient A of the above comparative examples was statistically analyzed, and it was found that it was indeed outside the range specified in the present invention, which was in line with expectations.
[0113] In summary: The present invention uses tin salt aqueous solution and sodium alginate sol of appropriate concentration as raw materials, and adds sodium chloride. By controlling the molar ratio of tin salt to sodium alginate and the molar ratio of tin salt to sodium chloride, a carbon-coated Sn composite material with a first coulombic efficiency higher than 60% is prepared by cross-linking reaction and multi-stage carbonization treatment. The preparation conditions are conventional, the operation is simple and the cost is low. In addition, the present invention also assists in screening carbon-coated Sn composite materials with excellent first effect and first week reversible capacity performance through simple mathematical calculations between parameters such as the concentration of the tin salt aqueous solution, the amount of sodium chloride added, the thickness of the carbon coating layer, the high-temperature carbonization temperature, and the lattice spacing of Sn. Therefore, the traditional negative electrode active material research and development requires a large number of assembled test batteries, which helps to reduce the research and development cost of negative electrode active materials, simplify research and development operations, and accelerate the research and development process.
[0114] Although embodiments of the present invention have been shown and described above, it should be understood that the above embodiments are illustrative and are not to be construed as limiting the present invention. Those skilled in the art may alter, modify, replace, and modify the above embodiments within the scope of the present invention. Furthermore, those skilled in the art may combine and incorporate the various embodiments or examples described in this specification, as well as features thereof, without conflicting requirements.
Claims
1. A carbon-coated Sn composite material having a carbon-coated Sn core-shell structure, characterized in that: The thickness of the carbon coating is 18-28nm, and TEM test shows that the lattice spacing of Sn is XRD test shows that the diffraction angle of Sn(101) peak is 31.84-32.02°, which also contains 306-387ppm of Na + .
2. The carbon-coated Sn composite material according to claim 1, characterized in that: When used as the negative electrode material for sodium ion batteries, the discharge cut-off voltage is 0V and the charge cut-off voltage is 2.0V under the charge and discharge test at a current density of 0.1C, and its capacity is greater than 540mAh / g. Preferably, its capacity is 541-586 mAh / g.
3. A method for preparing the carbon-coated Sn composite material according to claim 1, characterized in that: The steps are as follows: S1, dissolving a tin salt in water to form a tin salt aqueous solution, then adding sodium chloride, stirring and dissolving to form a mixed solution; S2, dissolving sodium alginate in water to form a sodium alginate sol; S3, adding the sodium alginate sol obtained in S2 dropwise to the mixed solution obtained in S1, performing cross-linking reaction at room temperature and centrifuging to obtain a white granular product, which was then dried; S4, subjecting the product obtained in S3 to a multi-stage carbonization treatment under an inert atmosphere to obtain a final product, wherein the multi-stage carbonization treatment includes pre-carbonization and high-temperature carbonization; Wherein: the concentration of the tin salt aqueous solution is represented by c, and the unit is mol / L; the amount of sodium chloride added is represented by a, and the unit is g; the thickness of the carbon coating layer in the composite material is represented by h, and the unit is nm; the temperature of high-temperature carbonization is represented by T, and the temperature is ° C; the lattice spacing of Sn in the composite material is represented by d, and the unit is nm; the above parameters meet the following requirements: 0.89≤c*a*h / (T*d)≤1.
44.
4. The method for preparing the carbon-coated Sn composite material according to claim 3, wherein: The molar ratio of tin salt to sodium alginate is 2.5-5, and the molar ratio of tin salt to sodium chloride is 0.59-1.18; Preferably, the concentration of the tin salt aqueous solution is 1-2 mol / L, and the mass percentage of the sodium alginate sol is 8%-12%.
5. The method for preparing the carbon-coated Sn composite material according to claim 3, wherein: In step S3, stirring is continued during the cross-linking reaction, the normal temperature refers to 16-25° C., and the cross-linking reaction time is 10-15 hours.
6. The method for preparing the carbon-coated Sn composite material according to claim 3, wherein: In step S4, the temperature of the pre-carbonization is 500-700° C. and the time is 0.5-5 h, and the temperature of the high-temperature carbonization is 900-1100° C. and the time is 2-6 h.
7. The method for preparing the carbon-coated Sn composite material according to claim 3, wherein: The tin salt is a +2-valent or / and +4-valent tin salt that is soluble in water.
8. A negative electrode sheet, characterized in that: Contains the carbon-coated Sn composite material according to claim 1 or 2 or the carbon-coated Sn composite material prepared according to the preparation method according to any one of claims 3-7.
9. A sodium ion battery, characterized in that: Contains the negative electrode sheet as claimed in claim 8.
10. The sodium ion battery according to claim 9, characterized in that: It passed the charge and discharge test at a current density of 0.1C, with a discharge cut-off voltage of 0V, a charge cut-off voltage of 2.0V, and an initial coulombic efficiency of >62%; Preferably, the first coulombic efficiency is 62.4%-67.6%.